Occurrence of itraconazole-tolerant micromycetes in the soil and food products - Piecková, E; Jesenská, Z (Folia microbiologica, 1999)
Unexpected pathogens from the environment represent considerable risk for humans with impaired health. We examined the occurrence of itraconazole tolerant micromycetes in soil and in maize products. Five concentrations of itraconazole (2.5-12.5 micrograms/mL) selected according to known treatment schedules for human patients were incorporated into Sabouraud agar with chloramphenicol and Rose Bengal and diluted samples were inoculated onto the agar surface. After 7-d growth at 22 degrees C colonies of Alternaria sp., Aspergillus clavatus, A. glaucus group, A. flavus, A. fumigatus, A. niger group, A. ochraceus group, A. ochraceus, Chaetomium sp., Cladosporium cladosporioides, Cylindrocarpon sp., Doratomyces sp., Fusarium sp., F. moniliforme, F. oxysporum, F. solani, F. subglutinans, Marianaea elegans, Mortierella sp., Mucor sp., Myrothecium sp., Penicillium sp., Rhizopus sp., Scopulariopsis brevicaulis, Sepedonium sp., Stachybotrys chartarum, Stemphylium sp., Torula humicola and Trichoderma viride were isolated.
Keywords: houby; Soil Microbiology; potravinářská mikrobiologie; Opportunistic Infections; kukuřice setá; Food Microbiology; antibiotická rezistence; Antifungal Agents; Microbial Sensitivity Tests; Itraconazole; Fungi; oportunní infekce; Zea mays; mykózy; Humans; půdní mikrobiologie; Mycoses; itrakonazol; Drug Resistance, Microbial; mikrobiální testy citlivosti; lidé; antifungální látky